Experimental and Numerical Failure Analysis of Adhesive Composite Joints - Farhad Asgari Mehrabadi (International Journal of Aerospace Engineering)
In the first section of this work, a suitable data reduction scheme is developed to measure the adhesive joints strain energy release rate under pure mode-I loading, and in the second section, three types of adhesive hybrid lap-joints, that is, Aluminum-GFRP (Glass Fiber Reinforced Plastic), GFRP-GFRP, and Steel-GFRP were employed in the determination of adhesive hybrid joints strengths and failures that occur at these assemblies under tension loading. To achieve the aims, Double Cantilever Beam (DCB) was used to evaluate the fracture state under the mode-I loading (opening mode) and also hybrid lap-joint was employed to investigate the failure load and strength of bonded joints. The finite-element study was carried out to understand the stress intensity factors in DCB test to account fracture toughness using J-integral method as a useful tool for predicting crack failures. In the case of hybrid lap-joint tests, a numerical modeling was also performed to determine the adhesive stress distribution and stress concentrations in the side of lap-joint. Results are discussed in terms of their relationship with adhesively bonded joints and thus can be used to develop appropriate approaches aimed at using adhesive bonding and extending the lives of adhesively bonded repairs for aerospace structures.